An education based on real contexts - Rosabal-Vitoria, Satya (2016)
This article describes the experience generated in the extension project “Models of Educational Management in Schools”, assigned to the Division de Educación para el Trabajo, CIDE-Universidad Nacional. Particularly the implementation of this project is at the Educational Region of Heredia, between 2011 and 2013, with the participation of 14 public schools at preschool and elementary level. During the development of this experience, we worked with different actors of the educational community in various educational institutions in building their pedagogical models based on the recognition of the characteristics of the context in which it is located each; creating opportunities for the integration of school dynamics in a common front and by performing groups diagnostic to establish institutional mechanisms for self-improvement. The process developed to implement the project was developed in three stages, during which actions as were made: the selection of schools needs assessment, awareness of the teams, the participatory development, implementation and monitoring and sustainability. When the process is achieved, each participating school count with a differentiated curriculum that responds to the particularities of context. Thus the region of Heredia, is strengthened in its educational processes by improving, strengthening and renewal of the curriculum.